Analisa dan Perancangan E-Learning Pembelajaran Pemrograman Dasar Kelas X SMK - Adi Pirmansah; Suharno Suharno; Siti Sutarmi Fadhilah (Teknodika, 2017)
This study aims to produce an E-learning design that will be used in basic programming learning in the Vocational High School Multimedia Skills Program. E-Learning is a learning technology that is bridged by internet technology in which there are media to display material, questions and discussion forums. E-Learning strongly supports the basic programming learning process, because basic programming is learning that requires every student to memorize or understand algorithms and programming languages that aim to be able to make a computer program. Students are required to learn repeatedly so that basic programming materials are not easily forgotten. With E-Learning, students can learn wherever and whenever they are so that the process of learning basic programming can be done anywhere and anytime repeatedly without having to face-to-face with the instructor. But not all E-Learning is able to meet the needs of every learning process of every education provider, because in general between one educational provider with another has different learning strategies and standards. Therefore, before developing E-Learning, it first requires the process of analysis, planning, and design in order to arrange the right framework according to needs.